2012
DOI: 10.3732/ajb.1200003
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite primers in Oenothera harringtonii (Onagraceae), an annual endemic to the shortgrass prairie of Colorado

Abstract: These results indicate the utility of these markers in O. harringtonii for future studies of genetic structure, gene flow, and parentage as well as their applicability in other members of the O. caespitosa species complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…After repeating these simulations with different combinations of the microsatellite markers described in Skogen et al . (), a set of seven markers was identified that maximized the resolving power of simulated paternity tests. Offspring were therefore assayed at these loci, and the parental data set (Rhodes et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After repeating these simulations with different combinations of the microsatellite markers described in Skogen et al . (), a set of seven markers was identified that maximized the resolving power of simulated paternity tests. Offspring were therefore assayed at these loci, and the parental data set (Rhodes et al .…”
Section: Methodsmentioning
confidence: 99%
“…Simulations were based on observed allele frequencies in the parental data set (Rhodes et al 2014) and were parameterized as follows: 10 000 simulated offspring, 350 candidate fathers, 95% of candidate fathers sampled, genotyping error rate of 1% and a minimum of four typed loci. After repeating these simulations with different combinations of the microsatellite markers described in Skogen et al (2012), a set of seven markers was identified that maximized the resolving power of simulated paternity tests. Offspring were therefore assayed at these loci, and the parental data set (Rhodes et al 2014) was truncated to match.…”
Section: Dna Extraction and Genotypingmentioning
confidence: 99%
“…DNA was quantified using a Nanodrop (Nano-Drop Technologies, Wilmington, Delaware, U.S.A.) and diluted to a final concentration of 50-100 mg/ml. All individuals were genotyped using 12 nuclear microsatellite markers (Skogen et al, 2012;Rhodes et al, 2014) and four plastid microsatellite makers (Lewis et al, 2016). The nuclear microsatellite markers were fluorescently labeled (WellRed D2, D3, or D4, Sigma-Proligo, St. Louis, Missouri, U.S.A.) while the plastid samples were labeled using a two-step polymerase chain reaction (PCR) (Skogen et al, 2012;Lewis et al, 2016).…”
Section: Molecular Datamentioning
confidence: 99%
“…However, given the small number of individuals used to perform the analysis (three per population), we cannot make any assumptions about the species' genetic diversity and genetic structure. When three populations were evaluated, the genetic variation found was lower than that reported for Oenothera harringtonii and Oenothera biennis, for which the same primers were developed and tested [47,48]. The number of alleles found in O. drummondii was lower for most markers tested.…”
Section: Discussionmentioning
confidence: 68%
“…We tested a combination of plastid and nuclear microsatellite loci and screened 28 published markers (nuclear: Oenbi2diA_C10, Oenbi2diA_E9, Oenbi2triA_A1, Oenbi2triA_A5, Oenbi2triA_C6, Oenbi2triA_D3, Oenbi2triA_E4, Oenbi2triA_F5, Oenbi2triA_H1, Oenbi2triA_H2, Oenbi39tri10, OenhaB105, OenhaC4, OenhaC105, OenhaC106, OenhaC126, OenhaD2, OenhaD5, OenhaD102, OenhaD111, OenhaD118, Oenbi2tri2, Oenbi39di2, Oenbi39tri4, plastid: OenelCp3, OenelCp5, OenelCp11, OenelCp12) [47][48][49]. Ten markers were designed for Oenothera harringtonii W.L.…”
Section: Primer Selectionmentioning
confidence: 99%